An integrative assessment of the taxonomic status of putative hybrid leopard frogs (Anura: Ranidae) from the Chortís Highlands of Central America, with description of a new species. Issue 4 (19th May 2018) - Luque-Montes, Ileana; Austin, James D.; Weinfurther, Kayla D.; Wilson, Larry David; Hofmann, Erich P.; Townsend, Josiah H.
Abstract : Integrative taxonomy seeks to approach the complex topic of species diagnosis using independent, complementary lines of evidence. Despite their ubiquity throughout North and Central America, taxonomy of the American leopard frogs (Anura: Ranidae: Rana : subgenus Pantherana ) remains largely unresolved, and this is arguably nowhere truer than in the Central American country of Honduras, where there are two nominal species, the taxonomy of which remains unresolved. Leopard frogs from several mountainous areas along the continental divide in Honduras have previously been considered putative hybrids between Rana brownorum and R. cf. forreri, as opposed to two alternate hypotheses: one that they represent a high-altitude eco-morph of a single widespread species that included both lowland forms, or a second that there is an undescribed highland species distinct from either of the recognized lowland forms. We examine this set of hypotheses using three independent lines of evidence. First, we used species distribution modelling to examine potential geographic isolation of the highland form and the two putative parental lowland species, and found strong ecological separation between the highland and lowland forms. Second, mitochondrial and nuclear DNA supports the distinction of the highland form from both putative parental species, with mtDNA data refuting the hypothesis that representatives of either species may represent a matrilineal founder. Morphologically, the highland form is significantly smaller than, and otherwise readily differentiated from, both R. brownorum and R. cf. forreri, as well as all other Rana found in Honduras and adjacent areas. As a result, we formally describe the highland leopard frog as a new species. http://zoobank.org/urn:lsid:zoobank.org:pub:BE53F587-3618-4433-9651-E495808E5474